An Integrative Review of Pain Resource Nurse Programs. Issue 1 (January 2016) - Crawford, Cecelia L.; Boller, Jan; Jadalla, Ahlam; Cuenca, Emma
Abstract : Mismanaged pain challenges health care systems. In the early 1990s, pain resource nurse programs were developed by Ferrell and colleagues. Variations of the model have existed for more than 20 years. While results of these programs have been disseminated, conclusive evidence has not been examined via a synthesis of the literature. A structured systematic search using multiple databases was conducted for research studies published 2005-2012. The search identified 11 studies on effective use of a pain resource nurse and/or a pain resource nurse program. The results revealed wide variations existing in program design, research methodology, practice settings, and reported outcomes. Overall, the strength of the evidence on pain resource nurse programs was determined to range from low to moderate quality for making generalizable conclusions. However, 4 key elements were identified as integral to effective pain resource nurse programs and useful for the program design and development: leadership commitment and active involvement in embedding a culture of effective pain management throughout the organization; addressing staff-related and organization-related challenges and barriers to pain management; a combination of strategies to overcome these barriers; and collaborative multidisciplinary teamwork and communication. Specific recommendations are provided for program implementation. Although the evidence was inconclusive, useful information exists to create the design of effective pain resource nurse programs. Collaborative multisite studies on the long-term effects of pain resource nurse programs are recommended.